A digital approach in the rapid response to COVID-19 – Experience of a paediatric institution. (May 2021) - Cheng, Daryl R; Coote, Andrew; South, Mike
Abstract: Introduction: COVID-19 has radically changed the delivery of healthcare in Australia. Central to a tertiary paediatric institution's (The Royal Children's Hospital Melbourne (RCH) response was a digital health approach comprising a broad suite of informatics and technology solutions including optimising a fully integrated electronic medical record (EMR). Methods: This comprehensive approach spanned all patient care areas and encompassed a broad range of hospital operations. They included patient triage, registration, COVID-19 screening clinic operations, electronic ordering, prescribing and documentation, telehealth, reporting and analytics and research. Discussion: This paper outlines key aspects of our COVID-19 digital health strategy, highlighting the rapid transition to telehealth and the development of a remote "virtual telehealth" strategy for clinicians which proved popular and allowed true "working from home". Conclusion: COVID-19 has inadvertently focussed the spotlight on the utility of digital health for clinical care. The speed and uptake of digital health within this pandemic has been remarkable and unprecedented in both an Australian and global setting. Whilst many of these changes have been beneficial, some may have been rushed or forced with minimal consideration of ongoing governance. Key stakeholders and enablers should be identified for post-pandemic consideration in future digital health implementation and adoption strategies.